2012
DOI: 10.1071/hc12123
|View full text |Cite
|
Sign up to set email alerts
|

Access to general practice for Pacific peoples: a place for cultural competency

Abstract: INTRODUCTION: Access to primary health care services has been identified as a problem for Pacific peoples. Although cost is the most frequently cited barrier to Pacific service utilisation, some research has indicated that access may also be influenced by features of mainstream primary care services. This study aimed to identify features of mainstream general practice services that act as barriers to accessing these services for Pacific peoples in order to explore strategies that providers could adopt to enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Establishing and maintaining a therapeutic connection is considered vital to the quality of any clinical interaction involving Māori and Pacific Islanders (Lacey, Huria, Beckert, Gilles, & Pitama, 2011;Ludeke et al, 2012;McLellan, McCann, Worrall, & Harwood, 2013). It is important that this relationship acknowledges cultural-specific beliefs and values in order to augment trust and receptivity to the input provided (Lacey et al, 2011;McLellan et al, 2013).…”
Section: Rehabilitation Processes and The Therapeutic Alliancementioning
confidence: 99%
“…Establishing and maintaining a therapeutic connection is considered vital to the quality of any clinical interaction involving Māori and Pacific Islanders (Lacey, Huria, Beckert, Gilles, & Pitama, 2011;Ludeke et al, 2012;McLellan, McCann, Worrall, & Harwood, 2013). It is important that this relationship acknowledges cultural-specific beliefs and values in order to augment trust and receptivity to the input provided (Lacey et al, 2011;McLellan et al, 2013).…”
Section: Rehabilitation Processes and The Therapeutic Alliancementioning
confidence: 99%
“…In a report on Pacific patterns in primary health care (Davis, Suaalii‐Sauni, Lay‐Lee, & Pearson, ), it was identified that Pacific patients were heavily concentrated in the most deprived areas with 45% of Pacific patients in decile 10. The reason for the lower proportion of Pacific patients in our study is likely to be multifactorial; with few NPs identifying as Pacific, access to health services reported as being more challenging because of cost, transport, and appointment availability as well as language barriers, poor communication, and rushed consultations (Ludeke et al., ). Further studies are needed to identify the extent to which NPs are improving access to those patients with the greatest health needs.…”
Section: Discussionmentioning
confidence: 84%
“…Lower awareness among this group may be due to lower levels of engagement with mainstream society compared to women in Fiji, leading to limited exposure to family planning information. Studies have found that, along with cost 30,31 and language, 32,33 cultural sensitivities are important barriers to accessing reproductive services 32,34 . Thus, although living in urban areas increases women's likelihood of being exposed to family planning messages, 35–37 iTaukei women's ability to make sense of the information being shared may be challenged by language barriers and cultural sensitivities, e.g.…”
Section: Discussionmentioning
confidence: 99%